Ovarian Microcystic Stromal Tumor: A Case Report and Literature Review - Deng, Lin; Feng, Dingqing; Liang, Jing; Luo, Jie; Ling, Bin (Frontiers in Medicine, 2020)
Background: Microcystic stromal tumour is a recently described subtype of ovarian tumour characterized by microcystic pattern and diffuse immunoreactivity for CD10, vimentin, and β-catenin and negative for EMA. However, its diagnostic criterion and standard treatment remain unclear. Case presentation: We report a rare case of a left side microcystic stromal tumour with diameter about 7 cm in a 25-year-old female and summarize all cases of MCST reported in this study. The present patient underwent left ovarian tumour resection. Generally, the tumour was solid and cystic mixed. Immunohistochemically, the tumour was expressed CD10, WT1, cyclin D1 and vimentin and nuclear immunoreactivity for β-catenin but negative for α-inhibin, calretinin, CK AE1/AE3, PLAP, SALL-4, CK7, P53, EMA, CD99, AFP, desmin, CgA, E-cadherin, and melanA. Conclusion: Unilateral ovary, solid-cystic, and a larger than 4 to 8 cm pelvic mass without serious abdominal pain are its clinical features. The immunophenotype of vimentin+/CD10+/WT-1+/β-catenin+(nuclei)/cyclin D1+ is supportive of diagnosis. For these patients, unilateral oophorectomy dissection could be selected